A Critical Analysis of the Quad -Segments in “Train to Pakistan,” an Epoch-making Novel by Khushwant Singh - Radheshyam Ilame, Dr. Veena (International Journal of Humanities and Education Development (IJHED), 2020)
This research paper aims to explore “Dacoity”, “Kalyuga” (the Age of Downfall), “Mano[1]Maira” (Dirty-Mind) and “Karma” (Deeds) in “Train to Pakistan”, an epoch-making novel inscribed by Khushawant Singh and critically analyse those four phases in the fiction. The Partition of India is the gloomiest occurrence in British India, which attracted the attention of several writers, poets, and novelists who portrayed it in their respective works. Khushwant Singh expresses his anger over the violation of the long-cherished Indian values over the communal riots that occurred over the process of the Partition of United British India into India and Pakistan. It can be argued that “Train to Pakistan”, a tragedy inscribed in a mock-comic form, heaps up pieces of criticism over the celebration of the freedom attained with mass murder, bestiality and ingeniously, delineating the pity and horror of the two-nation theory, and it is a nightmare with a thrilling texture which one closes the novel with a sigh of relief.